Design principles for doing business on second life : an immersive ethnographic study - Azeharie, Reza (2013)
This paper addresses the question of designing a virtual world business. A popular and economically thriving virtual world - namely Second Life 1 - was selected for the research investigation. From an extensive literature review, a conceptual framework was developed in order to model the four most thriving industries on Second Life: (1) Real Estate, (2) Building, (3) Fashion, and (4) Entertainment. A six-month immersive ethnographic study was conducted using two primary research techniques of participant observations and in-depth interviews. For each industry, the results are summarized according to the business areas that were deemed critical. The final section presents a synthesis of the integrated context to gain further insights on the industrial dependency among the four industries. The PARTS framework of Brandenburger and Nalebuff (1995) was used to synthesize design rules for the business owner operating in a virtual economy. The paper concludes by linking the act of fantasy fulfillment with the demand for virtual goods and services.